Evaluasi Pengiriman Dangerous Goods: Metode Analisis Six Sigma-DMAIC - Somadi, Somadi (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
During the delivery process of dangerous goods, several problems were found which caused company losses and consumer dissatisfaction. The aim of this research is to identify problems, factors causing problems and efforts to improve the dangerous goods delivery process. The research uses the six sigma analysis method with the DMAIC concept. Based on the results of the analysis, there were three problems that occurred, namely containers and trucks being rejected by customers, PIC not inputting MSDS and expired MSDS, and transporting dangerous goods not using trucks that had a B3 permit. The factors causing these three problems are supervision, behavior of drivers and PICs, feasibility and suitability of containers and trucks, timing of container selection, updating and merging MSDS, B3 permits, and number of B3 trucks. Efforts to improve delivery of dangerous goods include training on dangerous goods, socialization of HSE standards, maintenance of containers and trucks, changing container selection schedules, managing MSDS, obtaining B3 vehicle permits, auditing trucking vendors, and collaborating with other trucking vendors. Keywords: Dangerous Goods, DMAIC, Freight Forwarder, Six Sixma